Parent-Adolescent Communication on Sexual and Reproductive Health Issues : A Bibliometric Analysis - Rafazila, Ramli; Md Mizanur, Rahman; Gerraint, Gillan; Ahmad Sofian, Shminan; Rasitasam @ Razitasham, Safii; Jacey Lynn, Minoi; Stephanie Chua, Hui Li; Lee, Jun Choi (Horizon Research Publishing, 2025)
The study aims to analyze the research trends, collaborative networks, and evolving themes in parent-adolescent sexual and reproductive health (SRH) communication research from 2010 to 2024. A bibliometric analysis was conducted using the Web of Science (WoS) Core Collection database. The search, completed on May 23, 2024, used the terms “parent-adolescent communication” and “sexual and reproductive health” as search criteria. We identified 29 documents and exported the data in RIS format for analysis. VOSviewer software was employed to visualize co-authorship networks, keyword trends, and research hotspots. The analysis revealed significant shifts in research focus over time, from communication dynamics in 2019 to a stronger emphasis on adolescent SRH issues by 2020. Key research areas included public health, paediatrics, and psychology, with notable contributions from institutions such as Bahir Dar University, The Centres for Disease Control and Prevention (USA), and Makerere University. Collaborative networks identified highly active research groups, with researchers like Kemigisha E and Nyakato VN playing central roles. Keyword trends indicated a growing interest in topics such as HIV prevention, mental health, and adolescent risk behaviours. This study highlights the dynamic nature of parent-adolescent SRH communication research, emphasizing the importance of addressing evolving SRH challenges. Despite its reliance on a single database, the analysis provides valuable insights into research trends and collaborations. Future studies should incorporate multiple databases and broader publication types to enhance understanding and support effective policy development. Keywords Parent-Adolescent Communication, Sexual and Reproductive Health, Bibliometrics, Knowledge Graph, VOSviewer